Remote control of stepper motor position using RF / Liyana Fairuz Abdullah - Abdullah, Liyana Fairuz (2006)
This thesis describes the development of a Peripheral Interface Controller (PIC16F84A) with Radio Frequency (RF) remote control in controlling the position of the Hybrid Stepper Motor movement. The project undertaken was a one semester project which is divided into two parts; hardware development and software development. For hardware development, it consists of stepper motor driver circuit and peripheral interface board circuit. While for the software development, it consists of PIC16F84A Microcontroller program. The objective of this project is to interface Radio Frequency remote control with the PIC16F84A to control forward and reverse movement of the stepper motor. Besides that, the aim of this project is also to use the application of PIC16F84A interface with RF remote control to control the position of hybrid stepper motor. The PIC will receive the signal from Radio Frequency receiver where this signal represents the position of the transmitter's joystick (this position indicate forward or reverse movement). Then, PIC will process this signal and transmit the output signal to the stepper motor driver circuit to run forward and reverse movement of the motor step by step.